إعادة الإعمار في البنى التحتية لقطاع النقل - داؤد شفيق (Latakia University Journal -Engineering Sciences Series, 2018)
يقدم قطاع النقل الشروط الملائمة والمناسبة لتطور قطاعات الاقتصاد الوطني الإنتاجية والخدمية الأخرى، وتتصف علاقته مع هذه القطاعات بأنها علاقة تأثير متبادل، ما يعني أنه يتعذر تحقيق أي تقدم أو تنمية في أي من هذه القطاعات دون أن يسبقها أو يرافقها تقدمٌ ملموسٌ في قطاع النقل. لقد أولت الدولة هذا القطاع أهمية خاصة منذ فجر الاستقلال ،حيث خصص هذا القطاع بالاعتمادات الكبيرة في خططها الخمسية المتعاقبة. بعد عام 2000 حصلت هناك قفزة كبيرة في حجم الاعتمادات المخصصة لقطاع النقل، حيث بلغت هذه الاعتمادات في الخطة الخمسية التاسعة (2001-2005) ما يعادل ما أنفق على هذا القطاع في الخطط الخمسية السابقة مجتمعة. تعرض قطاع النقل وبناه التحتية (سكك حديدية، الطرق والجسور، المطارات ووسائل النقل المختلفة...) إلى أعمال تدمير وتخريب ممنهج من جراء الأزمة التي تشهدها سورية منذ آذار 2011، التي هدفت الى تقطيع أوصال البلاد وشل حركة الركاب والبضائع، ونتيجة لذلك فقد مني قطاع النقل بخسائر إقتصادية جمة في بناه التحتية ووسائل النقل، وقد تم استعراض هذه الخسائر في متن هذا البحث للسنوات 2011،2012، 2013 ،كما تم استعراض واقع قطاع النقل قبل الأزمة. نظراً لأهمية هذا القطاع ودوره الأساسي في إعادة الإعمار، كانت هناك حزمة من المقترحات والرؤى التي تم طرحها لإعادة إعمار البنى التحتية للقطاع نفسه كأولوية وتعزيز دور هذا القطاع في إعادة الإعمار والتنمية وفق محاور تنموية، وفي إطار تخطيط اقليمي شامل وتنمية مستدامة. ولعل أهم آثار الأزمة، كان قرار الدولة السورية في الاتجاه شرقاً في سياستها، الأمر الذي يؤثر بشكل مباشر على تنفيذ شبكات النقل وبناه التحتية ووسائل النقل. إنطلاقاً من هدف الربط بين البحار الخمسة ،الذي اعتبر هدفاً أعلى في الإطار الوطني للتخطيط الاقليمي، فقد تم استعراض بعض الرؤى التي يمكن أن تساعد في تحقيق هذا الهدف بغرض جذب النقل الدولي والعابر عبر سورية واستغلال موقعها الجغرافي المتميز كعقدة نقل ومواصلات، بما يفضي إلى زيادة في معدل النمو الاقتصادي، وبالتالي إلى رفع مساهمة قطاع النقل في الناتج الإجمالي المحلي. The transport sector provides suitable and appropriate conditions for the development of the various sectors of the national economy, productivity and other services. Its relationship with these sectors is characterized by a mutual influence relationship, which means that no progress or development can be achieved in any of these sectors without preceded or accompanied by significant progress in the transport sector. The government has given special importance to this division since the inception of independence, when the sector was allocated large provision in its successive five-year plans. After the year 2000, there was a big leap in the provision of the allocations assigned to the transport sector, where reached (to the ninth five-year plan (2001-2005)) the equivalent to the expenditure on this sector in the previous five-year plans combined. The systematic destruction and devastation of the crisis in Syria since March 2011 aimed at splitting the country and paralyzing the traffic of passengers and goods. As a result, the transport sector suffered heavy economic losses in its infrastructure and transportation. These losses were evaluated in this research for the years 2011-2012, 2013 and the state of the transport sector was reviewed before the crisis. In view of the importance of this sector and its key role in the reconstruction, there was a package of proposals and visions that were put forward for the reconstruction of the infrastructure of the sector itself as a priority and strengthening the role of this sector in the reconstruction and development within the framework of comprehensive regional planning and sustainable development. Perhaps the most important impact of the crisis was the decision of the Syrian state oriental direction in its policy, which directly affects the implementation of transport networks and infrastructure and means of transport. Based on the goal of linking the five seas, which have set a higher goal in the national framework for regional planning, some visions have been reviewed that can achieve this goal in order to attract international transport and transit through Syria and exploit its geographical position as a transport hub leading to an increase in economic growth rate To raise the contribution of the transport sector to GDP.